EVALUASI KINERJA BADAN PENGAWAS PEMILU DALAM MENGAWASI PELAKSANAAN PILKADA KOTA PADANG TAHUN 2018 - Putri, Isra Mulyani (journal of residu, 2019)
This research departs from the findings of various violations that occurred during the campaign and collection and counting of ballots. Indications of violations found such as campaigns that do not comply with KPU regulations and ASNs that are not neutral. From these problems it can be questioned how the performance of the Election Supervisory Body (Bawaslu) in the City of Padang in carrying out their duties and authorities. This study uses qualitative techniques that are descriptive. Informants of this research were determined with purposive sampling, that was the Coordinator of the Division of Violation Enforcement of the Election Supervisory Body, Head of the Legal Division and Supervisor of the Election Commission, Political Observer of Padang City and the community. This research used primary and secondary data derived from interview, and documentation study. The data analysis of this study uses the data analysis techniques of the Milles and Huberman models, namely data reduction, data presentation and conclusion drawing. Validity tested of this data used source triangulation technique, and than the data were analyzed with qualitative data technique.. The results of the study show that the task of the Bawaslu is to do more prevention than to take action either during the campaign period or the counting of ballot papers because the Bawaslu in executing cases of violations is not explicitly stated in the law. If a violation occurs Bawaslu must coordinate with related stakeholders